PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PADA SUBTEMA MANUSIA DAN BENDA DI LINGKUNGANNYA - Ita Annisa Rasyida Ismail; R. Teti Rostikawati; Mira Mirawati (STKIP Subang, 2023)
Ita Annisa Rasyida Ismail, 037119100. The Influence of Implementing the Project Based Learning Model on Student Learning Outcomes on the Subtheme of Humans and Objects in Their Environment. Primary School Teacher Education Study Program Thesis, Faculty of Teacher Training and Education, Pakuan University, 2023. This quasi-experimental research aims to determine the influence of learning outcomes on human and object sub-themes in the environment through the Project Based Learning model, by providing basic questions and designing projects that will made. This research was carried out at the Tlajung Udik 05 V B and V C Elementary Schools from June to July, even semester. The N-Gain calculation for the Project Based Learning model is 80 and the N-Gain value for the conventional model is 46, so the N-Gain in the experimental class is greater than the conventional class. Apart from this, a normality test was also carried out using the Lilliefors test, both samples had a normal distribution because the values for both samples were smaller than Ltable. In the Project Based Learning class, the value Lcount ≤ Ltable, namely 0.048 ≤ 0.161, and in the control class, the value Lcount ≤ Ltable, namely 0.095 ≤ 0.161. Then, in the homogeneity test, the data was homogeneous because it was smaller than X2 table, a value of 2.543 ≤ 1.85 was obtained. In the hypothesis test, the tcount of 8.979 was greater than the ttable of 2.302, indicating that H0 (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. Based on the research results above, it can be stated that the Project Based Learning model has an influence on the learning outcomes of human and object sub-themes in the environment, in other words the Project Based Learning model is more effective than the conventional model.